Nickel Sensitivity in Children Due to Using Stainless Steel Crowns: A Narrative Review - Ali Malekzadeh Shafaroudi; Pegah Nasiri; Azam Nahvi (Mazandaran University of Medical Sciences, 2021)
Context: Stainless Steel Crowns (SSC) are stable and durable restorations and a valuable technique in repairing deciduous teeth with extensive caries. Nickel and chromium are the main composing elements of SSCs, i.e. released in the oral environment; they can cause allergic reactions, especially in nickel-sensitive children. The symptoms of these reactions include gingival edema and the loss of alveolar bone. Evidence Acquisition: The required data used in our review were searched from articles published until 2020 and collected from online databases, including Scopus, PubMed, Google Scholar, and Science Direct, using "Nickel, Allergy, and SSCs" keywords. Articles concerning SSCs and their application, nickel allergy released from crowns, and their symptoms were included in this study. After the abstract screening, we recalled relevant studies for full-text review. Results: We are exposed to nickel every day in various forms; some individuals present hypersensitivity reactions when exposed to the slightest amounts of this metal. Nickel is a base metal and among the elements used in SSCs. Nickel is released from SSCs during the corrosion process in the oral environment. Excessively released nickel ions cause chronic fatigue syndrome, sensitive lymph nodes, muscle aches, and headaches. Conclusions: The amount of nickel released from SSCs is less than the number of other sources; thus, the immunological reactions of a large percentage of the population to this excess amount of nickel ions in the bloodstream are normal and cause no severe problems.